Signal Detection of Pediatric Drug–Induced Coagulopathy Using Routine Electronic Health Records - Nie, Xiaolu; Yu, Yuncui; Jia, Lulu; Zhao, Houyu; Chen, Zhenping; Zhang, Liqiang; Cheng, Xiaoling; Lyu, Yaqi; Cao, Wang; Wang, Xiaoling; Peng, Xiaoxia (Frontiers in Pharmacology, 2022)
Background: Drug-induced coagulopathy (DIC) is a severe adverse reaction and has become a significantly increased clinical problem in children. It is crucial to detect of DIC safety signals for drug post-marketing scientific supervision purposes. Therefore, this study aimed to detect potential signals for DIC in children using the routine electronic medical records (EMR) data. Methods: This study extracted EMR data from Beijing Children’s Hospital between 2009 and 2020. A two-stage modeling method was developed to detect the signal of DIC. We calculated the crude incidence by mining cases of coagulopathy to select the potential suspected drugs; then, propensity-score matched retrospective cohorts of specific screened drugs from the first stage were constructed and estimated the odds ratio (OR) and 95% confidence interval (CI) using conditional logistic regression models. The current literature evidence was sued to assess the novelty of the signal. Results: In the study, from a total of 340 drugs, 22 drugs were initially screened as potentially inducing coagulopathy. In total, we identified 19 positive DIC associations. Of these, potential DIC-risk of omeprazole (OR:2.23, 95% CI:1.88-2.65), midazolam (OR:1.88, 95% CI:1.59-2.23), voriconazole (OR:2.82, 95% CI:2.20-3.61) were three new DIC signals in both children and adults. Twelve associations between coagulopathy and drugs, meropenem (OR:3.38, 95% CI:2.72-4.20), cefoperazone sulbactam (OR:2.80, 95% CI:2.30-3.41), fluconazole(OR:2.11, 95% CI:1.71-2.59), voriconazole (OR:2.82, 95%CI:2.20-3.61), ambroxol hydrochloride (OR:2.12, 95% CI:1.74-2.58), furosemide (OR:2.36, 95% CI:2.08-2.67), iodixanol (OR:2.21, 95% CI:1.72-2.85), cefamandole (OR:1.82, 95% CI:1.56-2.13), ceftizoxime (OR:1.95, 95% CI:1.44-2.63), ceftriaxone (OR:1.95, 95% CI:1.44-2.63), latamoxef sodium (OR:1.76, 95% CI:1.49-2.07), and sulfamethoxazole (OR:1.29, 95% CI:1.01-1.64) were considered as new signals in children. Conclusion: The two-stage algorithm developed in our study to detect safety signals of DIC and found nineteen signals of DIC, including twelve new signals in a pediatric population. However, these safety signals of DIC need to be confirmed by further studies based on population study and mechanism research.